Desarrollo de una propuesta de inteligencia de negocios en el área de ventas de la empresa Amnufarvet utilizando la metodología Kimball. - Chicaiza Palate, Cynthia Jazmina (2022)
Business intelligence contributes significantly to the business sector, since it gives value to data as the most important intangible assets, which by transforming them into knowledge helps the manager and directors of an organization to make decisions. For this reason, it proposed to develop a business intelligence proposal for the sales area of the AMNUFARVET company as a support tool for its business management, based on the Ralph Kimball methodology because it has a highly versatile approach that is coupled with each requirement. business, thus achieving concrete and important results for the company. Using the visual and intuitive Power BI tool, the Dashboard created where the reports expressed in an agile and user-friendly way, the statistical reports generated present the best-selling categories and products, potential customers, months in which the highest and lowest recorded. Finally, the provinces and cantons that bill more entered. Thanks to the information obtained, the company optimizes the estimated time in carrying out business strategies, allowing it to improve its management, therefore, it concluded that a business intelligence solution improves competitiveness in the market, being an effective tool for decision making.